2019
DOI: 10.1021/acs.analchem.9b01813
|View full text |Cite
|
Sign up to set email alerts
|

Functional Fluorescence Microscopy Imaging: Quantitative Scanning-Free Confocal Fluorescence Microscopy for the Characterization of Fast Dynamic Processes in Live Cells

Abstract: Functional fluorescence microscopy imaging (fFMI), a timeresolved (21 μs/frame) confocal fluorescence microscopy imaging technique without scanning, is developed for quantitative characterization of fast reaction-transport processes in solution and in live cells. The method is based on massively parallel fluorescence correlation spectroscopy (FCS). Simultaneous excitation of fluorescent molecules in multiple spots in the focal plane is achieved using a diffractive optical element (DOE). Fluorescence from the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Valuable as a general approach for many cell types, with ImFCS we found that the membrane organization of resting RBL mast cells is predominantly Lo-like, as sensed by lipid probes, that protein modules in lipid-anchored probes modulate partitioning, and that diffusion of TM probes is selectively influenced by protein-based interactions. The simple analytical framework we describe to evaluate D distributions can be adapted readily to other spatially resolved fluorescence fluctuation methods (Ries et al, 2012;Wiseman, 2012;Digman et al, 2013;Bag and Wohland, 2014;Moens et al, 2015;Hendrix et al, 2016;Krmpot et al, 2019). In the context of mast cell activation, future studies will build on the foundation established here to examine stimulated signaling as mediated by the participating proteins within the environment of the responding membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Valuable as a general approach for many cell types, with ImFCS we found that the membrane organization of resting RBL mast cells is predominantly Lo-like, as sensed by lipid probes, that protein modules in lipid-anchored probes modulate partitioning, and that diffusion of TM probes is selectively influenced by protein-based interactions. The simple analytical framework we describe to evaluate D distributions can be adapted readily to other spatially resolved fluorescence fluctuation methods (Ries et al, 2012;Wiseman, 2012;Digman et al, 2013;Bag and Wohland, 2014;Moens et al, 2015;Hendrix et al, 2016;Krmpot et al, 2019). In the context of mast cell activation, future studies will build on the foundation established here to examine stimulated signaling as mediated by the participating proteins within the environment of the responding membrane.…”
Section: Discussionmentioning
confidence: 99%
“…proven valuable for discerning weak interactions underlying plasma membrane heterogeneity in the poised, steady-state, as sensed by distinctive probes and as modulated by the actin cytoskeleton. This simple analytical framework can be readily adopted in other spatially resolved fluorescence fluctuation methods (48,49,(93)(94)(95)(96)(97). In the context of mast cell activation, future studies will build on the foundation established here to examine stimulated signaling as mediated by the participating proteins within the environment of the responding membrane.…”
Section: Concluding Remarks Statistical Analyses Of D Distributions mentioning
confidence: 99%
“…In this aspect, machine-learning approaches are promising to not only automatize data analysis but also to remove human bias. Besides, machine learning has been employed to create tailor-made optimized designs for nanoantenna designs [ 130 ].…”
Section: Discussionmentioning
confidence: 99%